Pre- and postoperative need for pituitary hormone replacement in non-adenomatous sellar and parasellar lesions: importance of the sellar encroachment score - Waqar, Mueez (Acta Neurochir (Wien), 2020)
BACKGROUND: Pre-/postoperative pituitary endocrine deficiencies in patients with sellar/parasellar non-adenomatous lesions are poorly described and studies have not considered the effect of sellar invasion on endocrine outcome. The aim of this study was to relate the need for pituitary hormone replacement pre-/postoperatively, with sellar invasion, in non-adenomatous sellar/parasellar lesions. METHODS: Single-centre review of adults with histologically confirmed non-adenomatous sellar/parasellar lesion and follow-up ≥ 3 months or until postop radiotherapy. Pituitary dysfunction was defined by hormone replacement. The sellar encroachment score (0–6) was calculated as the sum of the thirds of radiological encroachment into the sellar region in the coronal and sagittal planes. Multivariate analysis with binary logistic regression was used to determine factors associated with pituitary hormone replacement. RESULTS: One hundred and seventeen patients were included with a median age of 49 years (range 16–84 years) and median follow-up of 13 months. Surgery was trans-sphenoidal (53%), trans-cranial (36%) or a combination (11%). The commonest histology types were meningioma (n = 33, 28%) and craniopharyngioma (n = 20, 17%). The median sellar encroachment score was 6 (range 0–6). Most (n = 86, 74%) did not require pituitary hormone replacement preoperatively. The need for pituitary hormones increased after surgery in 41 (35%) patients. In multivariate analysis, the sellar encroachment score was the only factor predictive of pre- (OR = 2.6, 95% CI = 1.2–5.5; p = 0.01) and postoperative risk of new pituitary hormone replacement (OR = 4.1, 95% CI = 1.7–10.1, p = 0.002). CONCLUSION: A significant proportion of these patients present with need for pituitary hormone replacement that may worsen postoperatively. The degree of sellar encroachment is predictive of pituitary hormone replacement status pre-/postoperatively.